Dimensión de autocuidado para la atención paliativa al adulto hipertenso Pungala-Puruhuay, 2017. - Coro Carrillo, Viviana Alexandra (2017)
TITLE: SELF-CARE DIMENSION FOR PALLIATIVE CARE OF HYPERTENSIVE ADULT OF THE HEALTH UNITS OF PUNGALA AND PURUHUAY, 2017. ABSTRACT: This research entitled "Self-Care Dimension for Palliative Care of Hypertensive Adult of the health units of Pungala and Puruhuay in Riobamba city, April-June 2017" was carried out with the aim of proposing nursing actions aimed at the development Self-care in the hypertensive patient. It was a descriptive- transversal research, with a mixed approach. The population to be investigated was formed by a group of patients (23) with a diagnosis of arterial hypertension. As a technique for data collection, the survey was used, through the test to assess the capacity and perception of self-care of the elderly in the community (CYPAC-AM), taken from and validated by Millán Méndez, in which it was evidenced Sociodemographic data: the female gender predominated with 73.91%, in the total hypertensive population. The majority of patients with a age range of 65 years or more predominate with 51.22%; Marital status: married with 69.57%, and in relation to instruction: basic with 82.61%. Regarding self-care perception categories, we measured the CYPAC-AM test for the measurement, 69.57% are in the category of perception of inadequate self-care and .43% are in a category of self-care perception Partially adequate. Conclusion: In this study, is evident that hypertension affects the health of the majority of older adults, who need help for their self-care by their relatives. Palliative care can help to achieve a better quality of life.